Demand articulation in the open-innovation paradigm - Fumio Kodama; Tamotsu Shibata (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
Background: In the marketing literatures, "articulation of demand" is quoted as an important competency of market-driving firms. In this paper, therefore, I will demonstrate how the concept of "demand articulation" was effective in formulating corporate policies for technology and market development, and also in government policies for accelerating the commercialization process of emerging technologies. Methods: In order to comprehend empirically what really means "demand articulation", i.e., how "market-driving" is different from "market-driven," we conducted a quantitative analysis of market growth paths in three different kinds of product categories. Results: We came to the arguments of "business model" creation, which will bring the concept of "demand articulation" into a reality under an emerging business environment of open innovation. Conclusions: In order for the concept of "open innovation" to be effective, the accumulation and advanced utilization of big-data is an absolute necessity. In other words, the combination of business model creation, accompanied by the accumulation of big data and its advanced utilization, can make the arguments of market-driving more plausible, and make the accuracy of demand articulation more enhanced. As far as business model itself is concerned, the experimentation and simulation of alternative business models becomes possible with the sheer existence of big-data. These are necessary conditions for IoT (Internet of Things) to be brought into a reality.
Keywords: 650